MEMBANGUN KERUKUNAN MELALUI KONSEP ESOTERISME DALAM TEKS TUTUR JATISWARA (STUDI FILSAFAT PERENNIAL) - I Komang Suastika Arimbawa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Religion is one of the sub parts that becomes the ‘spotlight’ when there is widespread conflict and violence. This is due to the displacement of spirituality-esoteric aspects in modern human life, so that in reality it is often found distortions of human values. In addition, the dynamics of community understanding are also still doctrinal and filled with the content of exclusivity in responding to plurality, as well as the erosion of respect for responding to horizontal conflicts. For this reason, the concept of esotericism in the text of Tutur Jatiswara is believed to be able to provide a theo-philosophical solution and build an inclusive-pluralist paradigm, and can be one of the guidelines for realizing a harmonious, peaceful and mutual assistance in helping joy and sorrow. Perennial Philosophy is seen as able to explain all the events that are essential, concerning the wisdom needed in carrying out the right life, which seems to be the essence or core of all major religions and traditions of human spirituality. This fact is the basis for the statement that all religions are the same in the esoteric area. There is no superior religion among other religions, because basically all religions are accommodating the “Truth and Absolute” of the One.